Fabrication of pyrimidine/g-C3N4 nanocomposites for efficient photocatalytic activity under visible-light illumination. (April 2019) - Zhuang, Jingguo; Zhang, Jing; Pang, Jingyu; Wang, Aijian; Wang, Xinhai; Zhu, Weihua
Abstract: In this work, a series of pyrimidine/g-C3 N4 photocatalysts has been synthesized via a facile solvothermal method for the first time. The structure, elemental composition and morphology of the photocatalysts were characterized by FT-IR, SEM, XPS, N2 adsorption-desorption isotherms and BET characterization methods. The photocatalytic activity of the pyrimidine/g-C3 N4 materials was investigated by the degradation of rhodamine solution under visible-light illumination. The pyrimidine/g-C3 N4 photocatalyst with 1 wt% of pyrimidine shows the highest photocatalytic activity for the degradation of RhB, which can be mainly ascribed to the effective interfacial charge transfer within the pyrimidine/g-C3 N4 photocatalyst and the cooperation effect of the excellent contact interface between g-C3 N4 and pyrimidine. The main active species during the photodegradation process are determined by the radical trapping experiments, proving that the superoxide radical (O2 − ) and the hydroxyl radical (OH) play the main role in the photocatalytic reactions. Highlights: A series of pyrimidine/g-C3 N4 photocatalysts has been synthesized. The content of pyrimidine has a significant effect on the photocatalysis. The enhanced photocatalysis is ascribed to the efficient charge transfer.